Chemoenzymatic synthesis of polypeptides containing the unnatural amino acid 2-aminoisobutyric acid. Issue 53 (9th May 2017) - Tsuchiya, Kousuke; Numata, Keiji
Abstract : Polypeptides containing 2-aminoisobutiryc acid (Aib) as an unnatural amino acid were synthesized via chemoenzymatic polymerization of the tripeptide ethyl ester AlaAibAla-OEt. Abstract : Polypeptides containing 2-aminoisobutyric acid (Aib) units as an unnatural amino acid residue were synthesized by papain-catalyzed chemoenzymatic polymerization of a tripeptide ethyl esterl -Ala-Aib-l -Ala-OEt in an aqueous medium. The Aib-containing polypeptide adopted an α-helix conformation in both the solid and solution phases, which was induced by the periodic Aib residue.